Risk management and its influence on the actions carried out at the control posts at the customs attendance of Tacna, period 2016 - Meza Falla, Néstor Edgardo (2019)
The development of this research work is focused on the aspects related to proper risk management, as a tool to minimize the possibility of error that may occur in control actions, taking into account that there is no intention to perform an act illicit until proven otherwise. The present research work is non-experimental because data are obtained directly from the reality under study, it is also descriptive, then explanatory and finally correlated according to the purpose of the research. The research area is framed in the customs control, establishing how the risk management influences the actions of control posts in the Tacna customs intendancy, through the strategic level, tactical level and operational level. Likewise, the lack of control actions by the customs administration has been observed, since the inspection of merchandise is necessary in order to be able to control the transit of goods according to the regulations in force, the immobilization and seizure does not have a adequate control for the lack of security measures and also operative control often do not have the necessary logistical support. So finally it is concluded that the implementation of adequate Risk Management significantly influences the actions taken in the Control Posts of the Customs office of Tacna, 2016 period.